Odpowiedzi

2009-11-10T16:03:09+01:00
A
x=3-y
3-y-2y=6

x=3-y
-3y=3/ dzielone przez -3

x=3-(-1)
y=-1

x=4
y=-1

B
2x+3y=5x-15
4x+20-2y+6=34

-3x=-15-3y / dzielone na -3
4x-2y=8

x=5+y
20+4y-2y=8

x=5+y
y=-6

x=-1
y=-6

C
2x-3x-3y+14=y-2
2x-2y+3y+3=2y-1

-x-4y=-16 /dzielone na -1
2x-y=-4

x=16-4y
32-8y-y=-4

x=16-4y
-9y=-36 / dzielone na -9

x=0
y=4

2009-11-10T16:29:25+01:00
A) x+y=3
x-2y=6

x+y=3
x=6+2y

6+2y+y=3
x=6+2y

3y=-3
x=6+2y

y= -1
x=6+2y

y= -1
x= 6 + 2 * (-1)

y= -1
x= 4

B) 2x+3y=5(x-3)
4(x+5)-2(y-3)=34

2x + 3y = 5x - 15
4x + 20 - 2y + 6 = 34

3y + 15 = 3x
4x - 2y = 8

y+5=x
4x - 2y = 8

y+5=x
4(y+5) - 2y = 8

y+5=x
4y + 20 -2y = 8

y+5=x
2y = - 12

y+5=x
y= -6

y+5=x
y= -6

-6 + 5 = x
y= -6

x = -1
y= -6

C) 2x-3(x+y)+14=y-2
2(x-y)+3y+3=2y-1

2x - 3x - 3y +14 = y - 2
2x - 2y +3y+3=2y-1

- 4y + 16 = x
2x - y = -4

- 4y + 16 = x
2 (- 4y + 16 ) - y = -4

- 4y + 16 = x
- 8y + 32 - y = -4

- 4y + 16 = x
-9y = -28

- 4y + 16 = x
y=28/9

-4 * 28/9 + 16 = x
y=28/9

112/9 + 16 = x
y = 28/9

112/9 + 144/9 = x
y = 28/9

x=256/9 = 28 i 4/9
y = 28/9 = 3 i 1/9